Mangostin-Rich Mangosteen Pulp Extract Improves Lipid and Protein Metabolism in Meat Goats - A. Tiantong; P. Khoinoi; K. Sasiwimonrit; S. Saengwong; W. Inyawilert; S. Khianngam; C. Lumsangkul (Faculty of Animal Science, IPB University, 2026)
The use of plant-derived bioactive compounds as natural feed supplements has gained increasing attention in ruminant production because of their potential to promote animal health and reduce the reliance on synthetic supplements and antibiotics. This study evaluated the effects of dietary supplementation with mangosteen peel powder (MPP) and mangosteen pulp extract containing 10% mangostin (MG10) on growth performance, hematological parameters, and metabolic profiles in meat goats. Overall, 25 male goats were divided into control, 1% MPP (MPP1), 2% MPP (MPP2), 1% MG10 (MG10-1), and 2% MG10 (MG10-2) groups. Hematological, serum lipid and sugar, serum protein, and liver function analyses were performed using blood samples, and feed intake and growth performance were examined. Growth performance did not differ significantly among groups; however, daily feed intake was significantly higher (p = 0.030) in the MG10-1 and MG10-2 groups than in the control group. Hemoglobin levels and red blood cell counts were unaffected by treatment and remained within normal ranges across all groups. MPP consumption increased aspartate aminotransferase activity and blood sugar levels. Conversely, MG10 supplementation, especially MG10-2, significantly elevated high-density lipoprotein (p = 0.007) and albumin levels (p = 0.014), whereas MG10-1 increased blood urea nitrogen and albumin levels. Low-density lipoprotein and cholesterol levels remained unchanged after supplementation. Overall, MG10 demonstrated greater potential than MPP as a functional feed additive because of its beneficial effects on lipid and protein metabolism. Thus, MG10 is a promising natural supplement for improving metabolic health and optimizing feed utilization in livestock production systems.